The Influence of Human Resource Training and Development on Employee Performance Through Job Satisfaction as a Mediating Variable - Lewaherilla, Novalien Carolina (Sean Institute, 2025)
This study aims to analyze the effect of human resource (HR) training and development on employee performance, with job satisfaction as a mediating variable at PT Pelabuhan Indonesia (Persero) Regional IV Ambon. The main problem raised is how HR training and development can improve employee performance directly and indirectly through increased job satisfaction. This study uses a quantitative approach with the Partial Least Square (PLS) analysis method through the assistance of SmartPLS 3.0 software. The research sample consisted of 50 permanent employees obtained through a purposive sampling technique. The analysis results show that training significantly influences job satisfaction, but does not directly impact employee performance. Conversely, human resource development has a significant impact both directly on performance and indirectly through job satisfaction. Furthermore, job satisfaction has been shown to act as a significant mediating variable in the relationship between training and human resource development and employee performance. These findings emphasize the importance of improving the quality of human resource training and development, as well as maintaining job satisfaction, to support optimal employee performance.